BLOOD PRESSURE DURING HEMODIALYSIS AS PREDICTOR OF MORTALITY IN END-STAGE RENAL DISEASE PATIENTS. (April 2021) - Zakauskiene, Urte; Vickiene, Alvita; Vicka, Vaidas; Sukackiene, Diana; Rimsevicius, Laurynas; Miglinas, Marius
Abstract : Objective: High blood pressure (BP) and consequential cardiovascular complications remain the leading cause of death in hemodialysis (HD) patients. Aim of this study is to link BP variations during HD with a 1 year mortality. Figure. No caption available. Design and method: We conducted a cohort study in tertiary reference dialysis center. Patients undergoing HD were enrolled. Systolic, diastolic and mean arterial BP were measured before, every hour during and after HD procedure. These patients were observed for 12 months and mortality rate was evaluated. Mean values of measurements were compared across the groups. Furthermore, these measurements were included in univariate and multivariate regression analysis, determining their potency to predict 1 year mortality. Results: Study enrolled 99 patients. Mean age of patients was 58.7 ± 14.4 years, more than a half of them were men 51 (51.5%) with median time on HD for 4, 5 [2, 0–8, 5] years. Mortality rate was 15.2 % (n = 15). All of the BP measurements were significantly lower in deceased group, except of BP before HD. (Table 1). Univariate regression analysis revealed that all of these pressures were linked to 1 year mortality, however, after application of stepwise forward selection model in multivariate analysis the most potent predictor was eluded to be MAP of the 1st HD hour (OR CI95% p), tripling the risk of mortality per every decrease of 10mmHg. However, the difference in precipitated risk of mortality for 2nd h, 3rd h and post HD MAP was minimal. Conclusions: One year mortality in HD patients is substantial. Blood pressure during and post HD is a more potent predictor of mortality than a blood pressure measured before the procedure. Further studies should investigate the application of intradialytic BP for the timely intervention.